Parent material and fire as principle drivers of foliage quality in woody plants - Ferwerda, J.G.; Siderius, W.; Van Wieren, S.E.; Grant, C.C.; Peel, M.; Skidmore, A.K.; Prins, H.H.T. (Forest ecology and management, 2006)
Identification of the factors that determine the variation in browse quality, as determined by their chemical composition, is an important step towards understanding herbivore distribution patterns. Therefore, the variation in leaf chemical composition (digestibility lowering compounds: condensed tannin and total polyphenol concentration, and nutrients: nitrogen and phosphorous concentration) was related to geomorphology, vegetation structure, and fire history, in mopane ( Colophospermum mopane) open woodland in Kruger National Park. The results show that the principle drivers of foliar nitrogen, condensed tannins and total polyphenols differ from those for foliar phosphorus. Nitrogen, condensed tannin and total polyphenol concentrations are mainly determined by the effect of fire. The foliar concentration of phosphorus is mainly determined by parent material. This difference may be related to differences in the mobility of nitrogen and phosphorous in the soil.